Patterns of Interpretation of Climate Change in Teachers' Statements and Consequences for Climate Communication in Teaching - Reinfried, Sibylle; Künzle, Roland (Journal of Geography Education, 2019)
Teacher language is an essential factor in the construction of meaning by learners. An explorative pilot study investigated how teachers communicate climate change. The aim was to discover frames of interpretation in teacher statements in order to generate supra-individual patterns of interpretation by using a combination of qualitative and quantitative methods. Interviews with eight secondary school teachers served as data source. Three patterns of interpretation could be identified, two of which can influence the interpretation of climate change among recipients in such a way that they can promote willingness to act, while the third pattern can inhibit motivation to act.
Keywords: Patterns of interpretation of climate change, framing, cluster analysis, climate communication, Education for Sustainable Development